(untitled) (Research, Society and Development, 2022)
Obesity is a global epidemic, with sedentary behavior being one of its main causes. In recent decades there has been a significant decrease in the levels of physical activity in different social strata, with young people being the most affected by this problem. In this context, this study aimed to investigate the level of sedentary lifestyle of students at the Escola de Referencia em Ensino Médio Herculano Bandeira, in the municipality of Paudalho, Pernambuco. A non-probabilistic study was carried out using a convenience sample, through a structured questionnaire, applied to a sample of 71 students. The results showed that 49.3% of the students did not practice walking; 38.0% did not practice any sport; 19.7% dedicate from 10 to 25 minutes to sports; 40.8% of students performed household chores alone; 29.4% dedicated 5 hours or more to social media; 38.0% did not have a defined number of meals; 84.5% associated a sedentary lifestyle with body inertia. The results show that the students consulted present sedentary behaviors, being insufficiently active and dedicating a lot of time to low-calorie activities, in addition to maintaining inadequate eating habits. The intervention of health and education professionals is necessary to reverse this worrying situation, allowing these young people to fully develop.